Strengthening the Adoption of Learner- Centred Pedagogies in Teacher Education in Uganda through Video-Based Self Reflection and College- Based Mentorship System - Kisalama, Robert; Ahumuza, Akiiki Emmanuel; Okurut, David Stephen (Baraton Interdisciplinary Research Journal, 2021)
The intermittent pedagogical support received by teacher-trainers from the central level makes it difficult to implement new practices in teacher training institutions in Uganda. This mixed-methods study, investigated teacher-trainers’ perceptions of a pilot pedagogical support system implemented by college-based mentors. Qualitative and quantitative data were elicited using an on-line questionnaire completed by teacher- trainers (n=100) and video-records of interviews with selected college-based mentors (n=6) who reflected on their own experiences to propose ways of improving the system. The findings revealed that irrespective of years of experience, teacher-trainers appreciate the contribution of college-based mentors towards the adoption of learner-centred pedagogy. It also revealed that the opportunity for a self- reflection and collegial critique afforded by video enhanced the practices of the mentees and greatly enriched the mentorship process. Nonetheless, the teachertrainers expressed the need to broaden mentorship activities to include subject -specific pedagogic support.
Keywords: Learner-centred pedagogy, college –based mentorship, reflective practice, video-records, selfreflection